Clinicopathological Features of Sessile Serrated Polyps in China: A Retrospective Study of a Tertiary Hospital - Zhi-Jie Wang,; Cheng Luo,; Lin-lin Zhao,; Shi-yu Li,; Hong-yu Fu,; Xiao-ju Su,; Zhao-Shen Li, (Turkish Journal of Gastroenterology, 2023)
Background: Serrated polyps have been recognized as the important premalignant lesions. In this study, we aimed to analyze the clinicopathological features of sessile serrated polyps and determine the association between sessile serrated polyps and synchronous advanced adenomas.Methods: Consecutive patients undergoing diagnostic or therapeutic colonoscopies (including 156 681 diagnostic colonoscopies) from 2011 to 2019 were included.Results: A total of 958 patients, including 699 (73%) males, were detected with at least 1 sessile serrated polyp, and 65.9% (n = 658) of sessile serrated polyps were located in the distal colon. Advanced serrated lesions accounted for 9.1% (n = 91) of all the sessile serrated polyp (n = 999). The types of SSP included flat type (953/999, 95.4%) and sub-pedunculated or pedunculated type (46/999, 4.6%). Meanwhile, there was no obvious evidence supporting the association between advanced adenomas and characteristics of advanced serrated lesions or sessile serrated polyps.Conclusion: Sessile serrated polyps seem to be more frequently seen in the distal colon of men in this study. However, more evidence is required to confirm the actual distribution of sessile serrated polyp in colon among Chinese people. There is still much room for improvement of sessile serrated polyp detection rate, and more importance should be attached to sessile serrated polyp both for pathologists and endoscopists.Cite this article as: Wang Z, Luo C, Zhao L, et al. Clinicopathological features of sessile serrated polyps in China: A retrospective study of a tertiary hospital. Turk J Gastroenterol. 2023;34(2):101-107.